The role of hardiness in reducing stress and suicidal ideation in a sample of undergraduates students - Abdollahi, Abbas; Abu Talib, Mansor; Yaacob, Siti Nor; Ismail, Zanariah (SAGE Publications, 2015)
Suicide is a serious and growing public health problem, and it remains a serious cause of death in the world; therefore, it is essential to increase our knowledge concerning the etiology of suicide among undergraduate students. Previous studies have shown that perceived stress increases vulnerability to suicidal ideation. However, factors that may explain the association have not been studied empirically. A cross-sectional study was conducted to examine hardiness as a potential mediator between perceived stress and suicidal ideation among undergraduate students. The participants comprised 500 undergraduate students from Malaysian public universities. They completed the Personal Views Survey, Beck Scale for Suicidal Ideation, and the Perceived Stress Scale. Structural equation modeling estimated that undergraduate students with low levels of hardiness were more likely to report suicidal ideation. As expected, hardiness partially mediated between perceived stress and suicidal ideation. Our findings demonstrated that lower hardiness and greater perceived stress significantly predicted suicidal ideation among undergraduate students. These findings reinforce the importance of hardiness as a protective and predictive factor against perceived stress and suicidal ideation among undergraduate students.